A retrospective analysis of the safety and efficacy of apixaban use after lung transplant. Issue 7 (3rd May 2021) - Reininger, Kevin A.; Sam, Teena; Patel, Raksha S.; Grazia, Todd J.; Naik, Chetan A.; Ausloos, Kenneth A.; Rosenblatt, Randall L.; Lam, In Lok L.
Abstract: Direct acting oral anticoagulants (DOACs) have become the mainstay of treatment for patients requiring anticoagulation for atrial arrhythmias and venous thromboembolism (VTE) but safety and efficacy has not been established in lung transplantation. This is a retrospective review of 28 adult lung transplant patients who were prescribed apixaban for stroke prevention in atrial arrhythmias or treatment of VTE between October 15, 2015 and December 31, 2018. The primary outcome was a composite of efficacy and safety measured by recurrence or breakthrough of stroke or thromboembolism and bleeding events. Seven patients were treated for atrial arrhythmias and 21 treated for VTE. Fifteen patients received CYP3A4 or P‐gp inhibitors at initiation of anticoagulation, and 4 of these patients received strong CYP3A4 inhibitors. During the follow‐up period, one breakthrough DVT and one clinically relevant non‐major bleed were observed. These data suggest that apixaban may be safe to use for lung transplant patients, and larger studies are warranted to assess long‐term outcomes as well as safety and efficacy of alternative DOACs.